النظر اللغويّ في معرفيّة الإمام جعفر الصّادق (ت148هــ) - الوائلي, أ.م.د .جمانة عبد المهـدي جاسم (Journal of College of Education, 2023)
Praise be to God, we praise Him, we seek His help, and we seek His forgiveness, and I pray upon Muhammad, His trustworthy servant and His honorable Messenger, and upon his pure and chaste family, the solid foundations of knowledge, and the preponderant weights of wisdom, and peace be upon him.         And yet, Imam Jaafar al-Sadiq left a great gift from his blessed, supremely eloquent speech, whose eloquence is irresistible, whose sea does not bleed, whose depths are not comprehended, and whose lust is not pursued, since the paths of rhetoric were humiliated for him, as his speech is among the approaches, the buildings are smooth, how not when he is from a house  They were known for their eloquence and eloquence, so they are - as Imam Ali (peace be upon him) said - “We are the princes of speech, and in us its veins grow, and upon us its branches let down (the words of Imam Ali, the collection of Al-Sharif Al-Radi, 2008 AD: 448); therefore, Imam Ali bin Al-Hussein (peace be upon him) said  ) "They expressed our conversation;  I am an eloquent people” (Al-Kulaini, 2002 AD, 1/68).         The words of Ahl al-Bayt (peace be upon them) included fragments and luminous glimpses that indicate a clear approach and insightful and distinct linguistic thought, especially what we have received from Imam Jaafar al-Sadiq (peace be upon him) (d. 148 AH).  It was set in the middle of the second century of the Hijra (Al-Baghdadi, 1093 AH: 3/343).         In this research, I have consistently explained the linguistic consideration of the knowledge of Imam al-Sadiq (peace be upon him) according to what we have received of his heritage in this regard.  Therefore, it was divided into five axes containing the most prominent clear and bright highlights of Imam Jaafar al-Sadiq in this field of knowledge.  It specialized in the linguistic explanatory aspect of the nomenclature, and finally the fifth axis that I devoted to a picture of the rhetorical aspect of Imam al-Sadiq (peace be upon him), and it is worth noting that the opinions, sayings, and rulings of Imam al-Sadiq (peace be upon him) were spread in separate books, which I adopted in this research.